USP38: an important regulatory factor in tumor malignant progression - Li, Junyan; Zhong, Jinghua; Ye, Jianming; Xiang, Yi; Yi, Qiang; Zhu, Gangfeng; Deng, Shifan; Wang, Xiangcai (Frontiers in Immunology, 2025)
Ubiquitin-Specific Protease 38 (USP38), a member of the deubiquitinating enzyme (DUB) family, exhibits a complex and context-dependent role in cancer progression. This review summarizes current research on USP38, highlighting its dual functionality as both an oncogene and a tumor suppressor in various malignancies. We detail the structural characteristics of USP38, its differential expression patterns across cancer types, and its impact on key cellular processes including proliferation, migration, invasion, and apoptosis. Mechanistically, USP38 regulates the stability and activity of crucial proteins involved in tumorigenesis, such as HDAC1/3, LSD1, KLF5, METTL14, c-Myc, and HIF-1α, as well as influencing signaling pathways like JAK2/STAT3. The intricate interplay and, in some instances feedback loops, between USP38 and its targets underscore its multifaceted role. Finally, we discuss the potential of USP38 as a therapeutic target, the challenges in developing specific inhibitors, and future research directions to fully elucidate its complex biology and clinical implications.